Commercially available organic manures on growth, yield and nutrient content of Burmese Grapes (Baccaurea ramiflora) (Journal of Biodiversity Conservation and Bioresource Management, 2022)
A pot experiment was carried out in the net house of the Department of Soil, Water and Environment, University of Dhaka to evaluate the effectS of different organic manures on the growth performance, biomass production, NPKS content in leaf, stem and root of Burmese grapes (Baccaurea ramiflora) and some chemical properties of post- harvest soil. Two-month old Burmese grapes seedlings were planted in different organic manure-treated soils (viz. ACI, BGF, Bhola, Green Life, Kazi, Modern, Mazim, Payel, Payel Earth, and Shebok). A significant variation was observed among the treatments. Compared to control treatment, application of organic manures exhibited a significant influence on the physiological growth, viz. plant height (30.4 - 34.06 cm), leaf area (64.2 - 71.30 cm2/plant), leaf area index (0.17 - 0.19), fresh weight (32.2 - 53.06 g/plant), and dry weight (22.09 - 41.24 g/plant) after 120 days of the experiment. The highest plant height, leaf area, leaf area index, fresh weight, and dry weight were recorded in Kazi, BGF, Payel and Payel Earth, respectively. Similarly, the concentrations of N, P, K, and S in leaf, stem and root, and their uptakes were found significantly higher than the control. The highest N, P, K and S uptake by leaf, stem and root ranged from 37.66 - 41.69 kg/ha, 0.70 - 0.92 g/ha, 66.19 - 84.926 kg/ha and 6.82 - 10.11 kg/ha, respectively. Protein content was the highest in Payel in leaf (8%) and root (5%), and stem (7%) in Modern manure treatment. The overall results revealed that Kazi and Payel manures might be better for raising strong and healthy Burmese grape seedlings.J. Biodivers. Conserv. Bioresour. Manag. 2021, 7(1): 63-72